Subcutaneous sarcoidosis masquerading as cellulitis. - Papadavid, Evangelia; Dalamaga, Marianna; Stavrianeas, Nikolaos; Papiris, Spiridon A (Dermatology, 2008)
Sarcoidosis is a multisystem disease encountered by general physicians as well as medical specialists. Subcutaneous sarcoidosis is not an uncommon clinical presentation of sarcoidosis and is challenging for physicians because it can mimic cellulitis or several chronic infections. Our patient presented with a swollen forearm and hand which were initially treated as acute cellulitis with antibiotics by general physicians but without any improvement. A skin biopsy showed granulomatous panniculitis but confirmation of the diagnosis of systemic sarcoidosis was based on the characteristic chest roentgenogram, the high CD4/CD8 ratio of T lymphocytes in bronchoalveolar lavage, and the typical 'panda' and 'lambda' signs on the (67)Ga scan. Such cases with atypical clinical presentation cause some difficulty in reaching the diagnosis but a skin biopsy as well as typical imaging and laboratory signs are usually important to establish the diagnosis of sarcoidosis, when invasive procedures cannot be performed to get confirmation from a second target organ.
Keywords: Biopsy; CD4-CD8 Ratio; Cellulitis; Diagnosis, Differential; Humans; Male; Middle Aged; Radionuclide Imaging; Sarcoidosis; skin